Дослідження ефективності використання розподілених баз даних у системах IIoT - Климаш, М.; Гордійчук-Бублівська, О.; Чайковський, І.; Костів, О.; Klymash, M.; Hordiichuk-Bublivska, O.; Tchaikovskyi, I.; Kostiv, O. (Видавництво Львівської політехніки, 2022)
роаналізовано основні особливості роботи систем промислового Інтернету речей. Визначено необхідність використання розподіленої архітектури та хмарних ресурсів для гнучкого організування роботи промислових систем. Досліджено роботу реляційних баз даних та визначено їх перевагу над нереляційними, зокрема, швидкість оброблення великих обсягів інформації та надійність обслуговування користувацьких запитів. Запропоновано використання розподіленої архітектури баз даних для підвищення ефективності обчислень. Визначено переваги залучення хмарних та розподілених технологій у системи IIoT, а також можливість вибирати найоптимальніші параметри залежно від вимог до роботи промислового виробництва.

The Industrial Internet of Things (IIoT) determines the transformation of centralized systems into decentralized, more flexible, and efficient ones. Cloud technologies allow much more optimal use of IIoT resources. In the paper, the main features of the Industrial Internet of Things systems were investigated and the problems of smart manufacturing were analyzed. The necessity of using distributed architecture and cloud resources for flexible industrial systems organization was determined. In addition, the advantages of distributed computing for big data processing were established. The preference for relational databases over non-relational ones for data processing and the reliability of user requests service were defined. As well, the peculiarity of the relational database’s operation was considered. For improving computational efficiency the use of a distributed database architecture was investigated. The benefits of involving cloud and distributed technologies in IIoT systems were determined. In this way, the possibility of choosing the most optimal parameters depending on the requirements for the industrial system productivity was defined. The opportunities for improving the quality of services in the Industrial Internet of Things by choosing the optimally distributed database architecture were determined.
Investigation on efficiency of using of distributed databases efficiency in IIoT systems
Keywords: бази даних; SQL; розподілені обчислення; databases; SQL; distributed computing; 621.391